CHEMOTYPIC OF ROSMARINUS OFFICINALIS L. ESSENTIAL OILS FROM EASTERN SIDE OF IRAQ - HAMID, SARAH ALI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The purpose of this study was to identify and characterize chemical constituents of Rosmarinus officinalis L. essential oils from Diyala Province, an eastern side of Iraq. Methods: Following hydrodistillation extraction of the leaves, gas chromatography–mass spectrometry (MS) was performed. Eighteen peaks were identified and compared to known compounds and MS patterns. Results: The two major components identified were eucalyptol (1,8-cineole) and L-camphor, and they represent 59% and 29%, respectively. In addition, α-terpineol, bornyl acetate, borneol, linalool, and β-terpineol were detected in 3.75, 2.83, 1.96, 1.22, and 0.65%, respectively. Conclusion: The present study showed that rosemary essential oils from Diyala Province of Iraq consisted mostly of oxygenated monoterpenes (>96%) and hydrocarbon monoterpenes are less than 1%. The latter suggest that hydrocarbon monoterpenes may undergo transformation due to atmospheric as well as microbiological metabolism which more studies are needed to confirm such suggestion.